2022
DOI: 10.1111/nicc.12782
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care professionals' perceptions of the quality of counselling provided in the ICU: A cross‐sectional study

Abstract: Background: Intensive care professionals (ICPs) have a key role in counselling adult intensive care unit (ICU) patients and their family members. The counselling provided to ICU patients and their family members can be described based on the content, implementation, benefits, and resources. Aims:The study had two specific aims: first, to assess ICPs' perceptions of the quality of counselling provided to ICU patients and their family members; and second, to explore which factors ICPs feel is associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…16 From Turkey, one study 17 identified the skin problems related to using personal protective equipment by ICU nurses, and another study 18 examined the relationship between alarm fatigue and the tendency to make medical errors among ICU nurses. A Finnish study 19 assessed intensive care professionals' perceptions of, and factors associated with, the quality of counselling provided to ICU patients and their family members. An Iranian study 20 In this issue, we also include three systematic reviews: one aimed at identifying a population of critically ill children who have the highest risk of developing venous thromboembolism, 32 one examined the effectiveness of music listening on sleep quality, psychological outcomes, and physiological outcomes of critically ill patients, 33 and one reviewed the available evidence of initial paediatric trauma care throughout the health care process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16 From Turkey, one study 17 identified the skin problems related to using personal protective equipment by ICU nurses, and another study 18 examined the relationship between alarm fatigue and the tendency to make medical errors among ICU nurses. A Finnish study 19 assessed intensive care professionals' perceptions of, and factors associated with, the quality of counselling provided to ICU patients and their family members. An Iranian study 20 In this issue, we also include three systematic reviews: one aimed at identifying a population of critically ill children who have the highest risk of developing venous thromboembolism, 32 one examined the effectiveness of music listening on sleep quality, psychological outcomes, and physiological outcomes of critically ill patients, 33 and one reviewed the available evidence of initial paediatric trauma care throughout the health care process.…”
mentioning
confidence: 99%
“…From Turkey, one study 17 identified the skin problems related to using personal protective equipment by ICU nurses, and another study 18 examined the relationship between alarm fatigue and the tendency to make medical errors among ICU nurses. A Finnish study 19 assessed intensive care professionals' perceptions of, and factors associated with, the quality of counselling provided to ICU patients and their family members. An Iranian study 20 compared muscle strength and ICU‐acquired weakness in COVID‐19 and non‐COVID‐19 patients admitted to the ICU.…”
mentioning
confidence: 99%